A Multifunctional Bichromophoric Nanoaggregate for Fluorescence Imaging and Simultaneous Photogeneration of RNOS and ROS. Issue 11 (20th June 2013) - Fraix, Aurore; Gonçalves, A. Ricardo; Cardile, Venera; Graziano, Adriana C. E.; Theodossiou, Theodossis A.; Yannakopoulou, Konstantina; Sortino, Salvatore
Abstract: We report the design, preparation, and properties of a nanoaggregate formed in phosphate buffer solution by a porphyrin–β‐cyclodextrin (β‐CD) conjugate and a nitric oxide photodonor tailored to fit the β‐CD cavity. The small nanoassembly with a diameter of about 13 nm exhibits the typical red fluorescence of the porphyrin chromophore. The empty cavity of the β‐CD unit in the nanoaggregate is able to accommodate the NO photodonor, thereby forming a supramolecular bichromophoric aggregate with diameter of about 16 nm. This nanoconstruct preserves the fluorescence of the porphyrin core and is able to generate nitric oxide and singlet oxygen under illumination with visible light. The nanoassembly internalizes in melanoma cells, can be mapped therein by fluorescence microscopy, and induces a significant level of cell mortality, probably due to the combined action of reactive nitrogen oxide species (RNOS) and reactive oxygen species (ROS). Abstract : A sweet way to tackle cancer : A supramolecular nanoaggregate based on a porphyrin–β‐cyclodextrin conjugate and a tailored NO photodonor is effectively internalized by cancer cells, can be easily mapped inside cells due to its satisfactory red fluorescence emission, and induces a good level of cellular death under the exclusive control of visible light stimuli, probably due to the combined action of RNOS and ROS.